Ventilación mecánica no invasiva en pacientes con edema agudo de pulmón - Valeria Susana, Arévalo Arévalo (2021)
The investigation that is projected was based on the documentary investigation which is directed the search and selection of data with bibliographic relevance, with the aim ofto gather up-to-date information on the effectiveness of the ventilation application mechanics as a supportive treatment in patients with acute pulmonary edema tofavor physiological and gasometric improvement, decrease in hospital stayand mortality.The study identified a total of 100 scientific articles, of which were included 35 scientific articles, which were validated using the PEDro scale, presenting a minimum assessment of 6 points, the original articles were found in the language English, Portuguese and Spanish, the same ones that contributed and corroborated the effectiveness of the Non-invasive mechanical ventilation in patients with acute pulmonary edema. The bases of data in which the greatest results of scientific articles were found were: PubMed,Elsevier, Science Direct, Scielo, European Journal Respiratory, and virtual libraries from university repositories, from which scientific articles were collected from from 2010 to the present year 2021.At the end of the study, it was concluded that acute lung edema represents a great problem especially in adult patients and older adults, after discussion of theThe authors were able to show that the application of non-invasive mechanical ventilation of Support and positive pressure are highly effective in patients with acute edema of the cardiogenic and non-cardiogenic lung from an extra-hospital, inpatient setting and rooms of intensive care units ICU. Key words: acute lung edema, non-invasive mechanical ventilation, pressure positive